Genome-Wide Identification and Characterization of Potato Long Non-coding RNAs Associated With Phytophthora infestans Resistance - Cao, Weilin; Gan, Liming; Wang, Chenchen; Zhao, Xuechen; Zhang, Mingyu; Du, Jinwen; Zhou, Shumei; Zhu, Changxiang (Frontiers in Plant Science, 2021)
Long noncoding RNA (lncRNA) is a crucial regulatory mechanism in plant response to biotic and abiotic stress. However, their roles in potato (Solanum tuberosum L.) resistance to Phytophthora infestans (P. infestans) largely remain unknown. In this study, we identified 3,094 lncRNAs and 33,150 mRNAs of potato from large-scale published RNA sequencing data. Characteristic analysis indicated that the similar distribution pattern of lncRNAs and mRNAs on the potato chromosomes, and the mRNAs were longer and more exons than lncRNAs. Identification of alternative splicing (AS) showed that there were total 2,724 lncRNAs generated from AS and the highest frequency (44.35%) of alternative acceptor (AA). The target genes of 213 specific lncRNAs from infected samples were involved in multiple resistance signaling pathways, such as ‘Plant hormone signal transduction’, ‘Photosynthesis’, and ‘Plant-pathogen interaction’. We performed R package TCseq to cluster 83 specific differentially expression lncRNAs (DELs) from resistance lines and found that the lncRNAs of cluster 6 were up-regulated. The lncRNAs were subjected to KEGG pathway enrichment analysis and the interactive network between lncRNAs and mRNAs was constructed by using GENIE3, a random forest machine learning algorithm. Transiently overexpression StLNC004 in Nicotiana benthamiana significantly suppresses P. infestans growth compared with control and the expression of extensin (NbEXT) the orthologue of StLNC004 target gene was significantly up-regulated in overexpression line. Together, these results suggested that lncRNAs play potential functional roles in potato response to P. infestans infection.